Crab diversity in tongke-tongke mangroves, east sinjai district, sinjai regency - Sabri, Muh.; Rustam, Aswar (STKIP Persada Khatulistiwa Sintang, 2025)
This study used a qualitative, exploratory approach to explore the diversity and distribution of crabs in the Mangrove Forest Area of Tongke-Tongke. This study aims to identify the crab species present in the area. Conducted in January 2023, the research focused on four stations representing two distinct zones within the mangrove ecosystem. Stations 1, 3, and 4 were situated in the rehabilitation zone, characterised by varying levels of vegetation density and substrate conditions, while Station 2 represented an ecotourism area with higher human activity. Observations identified 11 crab species across six families, each exhibiting distinct morphometric and ecological adaptations to their respective microhabitats. Environmental parameters, including substrate type, salinity, temperature, and dissolved oxygen, were found to significantly influence species distribution and diversity. The findings emphasize the ecological importance of mangroves as biodiverse habitats supporting specialized niches for various crab species. This study contributes valuable insights into the conservation and sustainable management of mangrove ecosystems, particularly in balancing ecological preservation and human utilization.